Masters of the word : how media shaped history, from the alphabet to the Internet - Bernstein, William J. (Grove Press ; Distributed by Publishers Group West, 2013)
From the birth of writing in Mesopotamia to the technologies of today, this work documents the technology of media, a revolutionary tool that allowed rulers to extend their control far and wide, giving rise to the world's first empires. In this book the author chronicles the history of media, starting with the origin of writing thousands of years ago in Mesopotamia. The revolutionary tool gave rise to the world's empires and the birth of drama and democracy. But it is not just new communication technologies that have changed the world, it is access to them. Vernacular bibles gave rise to religious dissent, but it was only when the combination of cheaper paper and Gutenberg's printing press drove down the cost of books by 97 percent that the fuse of Reformation was lit. The Industrial Revolution allowed information to move faster and farther than ever before, though it concentrated power and enabled totalitarian governments. With the twenty-first century boom of the mobile Internet, control of media has again spread, and the world is both more connected and freer than ever before. -- From back cover.